Analytical study of the private cost of cancer patients and their satisfaction with hospital services. Ghardaia hospital case study (Revue El-Wahat pour les Recherches et les Etudes, 2020)
In Algeria, cancer is a major health problem, and satisfaction is an important aspect that  hospitals must include to improve the quality of health services.     This article presents the results of a field study concerning the private cost of cancer patients and their satisfaction with hospital services in the wilaya of Ghardaia. The number of questionnaires distributed is 70 copies. And the number recovered amounts is 65 copies. The data will be processed by SPSS.       There are considerable sums going to the care of patients, and the average annual unit cost of cancer patients is 237386 DA. This observation raises the issue of equity which must remain at the center of public health concerns.     The results also indicate a generally encouraging level of satisfaction with the quality of health care and relations with the staff, however there is a high level of dissatisfaction linked to hygiene and catering. KEYWORDS: private cost, cancer patients, satisfaction, Ghardaia.